The Peggy Guggenheim Foundation - Venice. - Barr, Alfred H. Jr.; Read, Herbert; Sandberg, Willem (Venezia : Peggy Guggenheim Collection, 1968)
Appel, Karel ; Archipenko, Aleksandr ; Arman ; Armitage, Kenneth ; Arp, Hans (Jean) ; Bacci, Edmondo ; Bacon, Francis ; Balla, Giacomo ; Baziotes, William ; Boccioni, Umberto ; Boto, Martha ; Brancusi, Constantin ; Braque, Georges ; Brauner, Victor ; Brô, René ; Butler, Reg ; Calder, Alexander ; Campigli, Massimo ; Carrington, Leonora ; César ; Chadwick, Lynn ; Chagall, Marc ; De Chirico, Giorgio ; Congdon, William ; Corneille ; Cornell, Joseph ; Costa, Toni ; Dali, Salvador ; Davie, Alan ; Delaunay, Robert ; Delvaux, Paul ; Doesburg, Theo Ven ; Dorazio, Piero ; Drake, Teddy Millington ; Dubuffet, Jean ; Duchamp, Marcel ; Duchamp-Villon, Raymond ; Dzamonja, Dusan ; Ernst, Max ; Falkenstein, Claire ; Ferren, John ; Fini, Leonor ; Francis, Sam ; Giacometti, Alberto ; Gleizes, Albert ; Gonzales, Julio ; Gorky, Arshile ; Gribaudo, Ezio ; Gris, Juan ; Guzman, Alberto ; Hare, David ; Hartigan, Grace ; Hausmann, Raoul ; Hayter, Stanley William ; Hélion, Jean ; Hirshfield, Morris ; Hundertwasser ; Irwin, Gwyther ; Jorn, Asger ; Kandinsky, Wassily ; Kemeny, Zoltan ; Klee, Paul ; Koenig, Fritz ; de Kooning, Willem ; Kupka, Frantisek ; Lassaw, Ibram ; Laurens, Henri ; Leger, Fernand ; Lipchitz, Jacques ; Lissitzky, El ; Mack, Heinz ; Magritte, René ; Malevich, Kasimir ; Man Ray ; Marcoussis, Louis ; Marini, Marino ; Massironi, Manfredo ; Masson, Andre ; Matta (Roberto Antonio Sebastian Matta Echaurren) ; Metzinger, Jean ; Minguzzi, Luciano ; Mirko ; Miro, Joan ; Mondriaan, Piet ; Moore, Henry ; Motherwell, Robert ; Nele, E.R. ; Nicholson, Ben ; Oelze, Richard ; Okada, Kenzo ; Ozenfant, Amédée ; Paolozzi, Eduardo ; Pegeen ; Pevsner, Antoine ; Picabia, Francis ; Picasso, Pablo ; Pollock, Jackson ; Pomodoro, Arnaldo ; Prampolini, Enrico ; Richier, Germaine ; etc.
biografie
Text French-English
boek